Privatization And Redistribution Of Property In The Uzbekneftegas System - Khusainov Ravshan Rakhimovich (Zien Journals, 2022)
In the article, the author considers the essence of privatization, denationalization, the formation of a market economy. As well as structural changes in the Uzbekneftegaz system.
Keywords: privatization; denationalization; economic policy; state policy